RARE-09. Treatment of childhood-onset craniopharyngioma patients using proton beam therapy versus photon-based radiation therapy in the prospective KRANIOPHARYNGEOM 2007 trial. (3rd June 2022) - Friedrich, Carsten; Boekhoff, Svenja; Sowithayasakul, Panjarat; Eveslage, Maria; Bison, Brigitte; Timmermann, Beate; Müller, Hermann L
Abstract: BACKGROUND : Proton beam therapy (PBT) compared to photon-based radiotherapy (XRT) offers the benefit to administer lower radiation doses to critical organs thereby possibly minimizing the risk of sequelae in patients with residual craniopharyngiomas (CP) after hypothalamus-sparing surgery. The validation in large CP patient cohorts is still pending. PATIENTS AND METHODS : Of 290 childhood-onset CP patients included 2007-2019 in the prospective multicenter trial KRANIOPHARYNGEOM 2007, 99 (34%) received external RT (65% PBT, 35% XRT). Outcome was compared between the different groups in terms of overall (OS) and event-free survival (EFS), quality of life (QoL using PEDQOL), functional capacity (FMH), and auxological data (BMI and height SDS) one, three and five years after irradiation/CP diagnosis. RESULTS : PBT became the predominant irradiation technique during the study period (used in 23% and 77% of all irradiated patients registered within the first and second half of the enrollment period, respectively). PBT as well as XRT were associated with high (p<0.001) EFS (PBT: 0.917 ± 0.040; XRT: 0.940 ± 0.041) compared to non-RT (EFS: 0.669 ± 0.044). OS was similar in all groups. No differences between PBT, XRT and non-RT CP patients concerning functional capacity and anthropometric parameters (height SDS, BMI SDS) have been obtained. Only in the PEDQOL domain "physical function", proxy-assessed QoL was lower one year after PBT when compared to XRT treated and non-irradiated CP patients. CONCLUSION : PBT is similar efficient in preventing relapses and recurrences in childhood-onset CP patients. During follow-up, no clinically relevant differences between PBT and XRT in terms of QoL, functional capacity and degree of obesity as a marker of hypothalamic syndrome were detectable. While PBT is increasingly applied, studies on larger CP cohorts with longer follow-up after RT are warranted to analyze, whether it can prevent sequelae such as hypothalamic syndrome and severe obesity compared to XRT.